Taxonomic Study On The Angiosperms Of Char Kukri Mukri Wildlife Sanctuary, Bhola District - Uddin, Mohammad Zashim; Md Abiabdullah, - (Journal of the Asiatic Society of Bangladesh, Science, 2016)
The paper presents the status of angiospermic flora of Char Kukri Mukri Wildlife Sanctuary, a small Island in the Bay of Bengal close to the Char Fassion Upazila of Bhola district. A total of 277 plant species belonging to 76 families was identified from the Island. For each plant species data on scientific name, local name, family, life form and habitat were provided. Trees of this Island were represented by 91, shrubs by 33, herbs by 118 and climbers by 35 species. The plant species recorded from the island were distributed in different habitats. Among the habitats, maximum species were recorded in homesteads (104) followed by roadsides (79), mangrove areas (47) and cultivated land (47).The study has reported the presence of medicinal plants, wildlife supporting plants, exotics and invasive plants, rare and threatened plants in the Island. The presence of fruit bearing species in the island is very rare because of high salinity. The introduction of exotics and invasive species into the Island has been recognized as the great challenges to the local angiospermic flora in future. This article also highlights the conservation values, management concerns and some measures for conservation of angiosperm diversity in the Island. Asiat. Soc. Bangladesh, Sci. 42(2): 153-168, December 2016